Precarious positions: glass ceilings, glass escalators, and glass cliffs in the superintendency - Timmer, Jennifer D.; Woo, David S. (Frontiers in Education, 2023)
The "glass cliff" phenomenon has been observed in many fields; in these situations, women are hired into prestigious, but precarious, leadership positions. In education, little is known about the preexisting district contextual trends into which women leaders are hired, and thus whether a glass cliff might exist in the superintendency. This study explores descriptively whether evidence suggests superintendents in New Jersey might be differentially sorted into "precarious" districts across gender. Our study utilizes a newly created statewide longitudinal data set to examine descriptive trends in superintendent placement, including multiple measures of precarity. We investigate the presence of the glass ceiling by examining representation in the superintendency, the glass escalator as evidenced by leader qualifications, and the glass cliff as indicated by district characteristics. New Jersey employs a higher proportion of women superintendents than the national average. Men and women superintendents are equivalently qualified, on average, though women tend to be paid less. We find that male and female superintendents in the state work in somewhat similar districts, though women are more likely to lead districts serving students from low-income communities and larger proportions of minoritized students. These findings suggest women superintendents in New Jersey are excelling despite serving communities that are often under-resourced. Thus, there is some suggestion of a glass cliff phenomenon in education leadership, as women who obtain the highest positions are also in more precarious settings.The "glass cliff" phenomenon has been observed in many fields (Cook & Glass, 2013;Ryan et al., 2016;Ryan & Haslam, 2005;White, 2023); in these situations, women are hired into ostensibly prestigious, but precarious, leadership positions. The concept was first introduced by Ryan and Haslam (2005) to describe the possible relationship between the appointment of women board